Effectiveness of Short Wave Diathermy and Therapeutic Ultrasound on The Management of Patients With Knee Osteoarthritis - Manhal, falah; Mecheser, Abdullah; Hussein, suhad (Iraqi National Journal of Nursing Specialties, 2007)
Objective : The present study is aimed to evaluate the effectiveness of short wave diathermy and ultrasound therapy for the management of patients with knee osteoarthritis Methodology : all patients who referred to the Medical Rehabilitation Unit in Baghdad Teaching Hospital and Sadr A!-Qanat Center. The period of the study was from October 2004 to April 2005, total number of patients was 24 (9 male and 15 female). Age range of patients was 42-70 years. Complete clinical and radiological examinations were achieved on all patients and referred to the Medical Rehabilitation Unit for physiotherapy. Short wave diathermy and ultrasound therapy were applied on all patients. Results : Demographic distribution revealed that female gender, the ages more than 50 year, the weight with grade II obesity were the most affected. Clinical observations indicated that chronic and severe cases were the most obvious. The study revealed that deformity, muscle wasting, local inflammation, and effusion were recorded in most patients. Outcomes of treatment with short wave and ultrasound therapies were nearly equally regarding their well-effectiveness, patient’s acceptance, and patient’s improvement. It was concluded that the ultrasound therapy is more preferable than short wave diathermy in the management of oedema accompanying chronic knee osteoarthritis. Recommendation : Further cohort studies are required to evaluate the effects of these procedures on a large sample of patients